Interconnection between aggression and protection factors of gastric juice and oral liquid of the patients with precancerous changes of gastric mucosa - A. I. Rudenko; L. M. Mosiychuck; O. M. Khomenko; O. P. Petishko (Kazimierz Wielki University, 2019)
This article is about learning of the aggression factors and the gastric juice and oral liquid protection of the patients with precancerous changes in the mucous gastric membrane of stomach. 32 middle-aged people were researched, who were at the inpatient treatment at the SI "Institute of Gastroenterology of NAMS of Ukraine": 6 of them were with the atrophic changes of mucous membrane of stomach with different rate of severity (the I group), 12 people were with the intestinal metaplasia in the antrum (the II group), 14 patients were with intestinal metaplasia in the body and in the antrum of mucous membrane of stomach (the III group). The diagnosis was established after meticulous endoscopic and histological researches of biopsy material of mucous membrane of stomach. During the esophagogastroscopic research the gastric juice was being collected. It was determined its pH, pepsin, glycoprotein, sialic acids, fucose and hexosamines concentration. Also there were conducted the investigations of oral liquid, where the content of glycoprotein, sialic acid, fucose and hexosamines was determined. In the gastric juice of patients of the II and III groups, the content of sialic acids was increased, in the III - the acid secretion increased the hexosamines, with anacid - of fucose and it was decreased the amount of pepsin. In the oral liquid, the content of sialic acids in all researching groups was increased, fucose - only in the I group, hexosamines and glycoproteins - only in the III group. The further complex study of functional-morphological changes of gastric secretion and salivary glands activity will allow to assess the condition of reserve capabilities of the protection factors of the mucous membrane of the stomach and to determine the risk groups of patients with the precancerous condition.